1996
DOI: 10.1063/1.117774
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering of alternating nanocrystalline silicon/amorphous silicon multilayers

Abstract: Nanocrystallite size distribution and structural properties in alternating hydrogenated nanocrystalline silicon/amorphous silicon multilayers were investigated by means of Raman scattering. The obtained Raman spectra show a broad peak at ϳ480 cm Ϫ1 from amorphous Si and some small peaks superposed on the broad peak. According to the positions of the crystallite peak, the mean crystallite size and volume fraction of the crystalline were calculated. Since these small peaks have strong size dependence of their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…The broad shoulder near the nanocrystal Si peak of 513.5 cm −1 can be observed. As shown in Figure 1(b), we have deconvoluted the spectrum to obtain the peak centered at a wavenumber of 513.5 cm −1 which belongs to the nanocrystal Si, and four broad peaks which are the characteristic peaks of amorphous silicon at wavenumber of 480 cm −1 (transverse optical mode), 380 cm −1 (longitudinal optical mode), 301 cm −1 (longitudinal acoustic mode), and 150 cm −1 (transverse acoustic mode) [34][35][36][37][38][39]. The Raman spectrum analysis has revealed that nanostructured silicon and amorphous silicon were generated simultaneously during the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The broad shoulder near the nanocrystal Si peak of 513.5 cm −1 can be observed. As shown in Figure 1(b), we have deconvoluted the spectrum to obtain the peak centered at a wavenumber of 513.5 cm −1 which belongs to the nanocrystal Si, and four broad peaks which are the characteristic peaks of amorphous silicon at wavenumber of 480 cm −1 (transverse optical mode), 380 cm −1 (longitudinal optical mode), 301 cm −1 (longitudinal acoustic mode), and 150 cm −1 (transverse acoustic mode) [34][35][36][37][38][39]. The Raman spectrum analysis has revealed that nanostructured silicon and amorphous silicon were generated simultaneously during the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the aforementioned near-surface states, which are excluded from the one-phonon connement model in Raman simulations, may cause exciton localization and thus can be PL active. 21,32 As a consequence, the size information these states contain may be included in PL simulations similar to defectrelated emissions. Therefore, a s in between the range of Raman and PL extracted values can be a reasonable good approximation of Si QDs size distribution skewness.…”
Section: 27mentioning
confidence: 99%
“…Si QDs embedded in an amorphous matrix (either amorphous Si or dielectric material) tends to have a coreshell structure, in which the nanoscale Si crystalline core is surrounded by an outer shell. 20,21 The outer shell consists of nearsurface ne sized crystalline phases with irregular shapes, which gradually transits to amorphous Si phases (a-Si) before reaching the amorphous matrix. [21][22][23][24] The presence of the nearsurface crystalline phases manifests itself as a weak intermediate peak near 500-510 cm À1 in Raman spectrum.…”
Section: 14mentioning
confidence: 99%
“…This peak was attributed to a defective part of the nano sized small crystalline phase originating from either crystallites with diameters less than 10 nm, a silicon wurzite phase resulting from twins, or bond dilation at grain bound- aries. 10)12) The nanocrystalline size in the amorphous silicon matrix could be estimated using the following formula:…”
Section: Resultsmentioning
confidence: 99%